Effects of Autogenous Bone Marrow Aspirate Concentrate on Radiographic Integration of Femoral Condylar Osteochondral Allografts. (October 2017) - Oladeji, Lasun O.; Stannard, James P.; Cook, Cristi R.; Kfuri, Mauricio; Crist, Brett D.; Smith, Matthew J.; Cook, James L.
Background: Transplantation of fresh osteochondral allografts (OCAs) is an attractive treatment option for symptomatic articular cartilage lesions in young, healthy patients. Because the lack of OCA bone integration can be a cause of treatment failure, methods for speeding and enhancing OCA bone integration to mitigate this potential complication are highly desirable. Purpose: To determine if autogenous bone marrow aspirate concentrate (BMC) treatment of large femoral condylar OCAs would be associated with superior radiographic OCA bone integration compared with nontreated allografts during the critical first 6 months after surgery. Study Design: Cohort study; Level of evidence, 3. Methods: A review of patients enrolled in a prospective registry who were treated with transplantation of large OCAs to one or both femoral condyles at our institution from March 12, 2013 to March 14, 2016 was performed. Patients were stratified into 2 groups based on BMC treatment versus no BMC treatment; the treatment was nonrandomized and was rooted in a shift in practice and a continuing effort to optimize OCA transplantation at our institution. Patients were excluded if they did not have orthogonal view radiographs performed at 6 weeks, 3 months, and 6 months postoperatively. Each condyle undergoing OCA transplantation was assessed individually by an independent musculoskeletal radiologist, who was blinded to the treatment group and time point. OCAs were assessed with respect to graft integration (0%-100%; 0 = no integration, 100 = complete integration) and degree of sclerosis (0-3; 0 = normal, 1 = mild sclerosis, 2 = moderate sclerosis, and 3 = severe sclerosis) of the graft at each time point. Results: This study identified 17 condyles in 15 patients who underwent OCA transplantation without BMC and 29 condyles in 22 patients who underwent OCA transplantation with BMC. The BMC group had significantly ( P = .033) higher graft integration scores at 6 weeks, 3 months, and 6 months after surgery. Graft sclerosis was significantly ( P = .017) less in the BMC group at 6 weeks and 3 months, with no significant difference at 6 months after surgery. When combining the groups to examine the influence of smoking on graft integration, nonsmokers had significantly ( P = .007) higher graft integration scores at 6 months. Conclusion: Large femoral condylar OCAs treated with autogenous BMC before implantation showed superior radiographic integration to bone and less sclerosis during the initial 6-month postoperative period. BMC treatment of OCAs may mitigate the failure of OCA bone healing.